Use of quantitative mass spectrometry-based proteomics and ELISA to compare the alpha 2 macroglobulin concentration in equine blood-based products processed by three different orthobiologic devices - Ortved, Kyla F.; Alward, Larry; Cowles, Bobby; Linardi, Renata; Barot, Dhvani; Usimaki, Alex; Fedie, Joseph R.; Amodie, Deb; Goodrich, Laurie R. (Frontiers in Veterinary Science, 2024)
Alpha 2 macroglobulin (A2M), a multi-functional protein in the plasma protease inhibitor class, regulates pro-inflammatory cytokines and the clearance of chondro-destructive enzymes in cases of joint injury and osteoarthritis (OA). When concentrated from whole blood, autologous A2M can be administered as a point-of-care option for intraarticular treatment of traumatic joint injury.The purpose of this study was to compare A2M concentrations in equine plasma samples processed by three commercial devices developed for stall-side regenerative joint therapy.Plasma samples were obtained from healthy adult horses (N = 13). Mass spectrometry analysis was used to determine the concentration of protein analytes in each sample. Selected reaction monitoring measured a specific A2M peptide as a surrogate of the whole A2M protein. A2M concentrations produced by each test device were compared for two sample types, a preconcentrate or platelet-poor (PP) component, and final component for use in the horse. There was no significant difference (P > 0.05) in the geometric mean (GM) concentration of A2M in the final concentration samples produced by the Alpha2EQ ® device (N horses = 13) and the single-centrifugation, PP samples produced by the Pro-Stride ® APS (autologous protein solution) device (N = 13) and the Restigen ® PRP (platelet-rich plasma) device (N = 11). When A2M content in final concentration samples produced by each device was compared, the Pro-Stride APS and Restigen PRP samples had a significantly greater GM A2M content (P < 0.0001) compared to the Alpha2EQ samples, and the Pro-Stride APS final concentration samples had a significantly greater GM A2M concentration (P < 0.0001) versus that for the Restigen PRP final samples. This comparison demonstrated that the volume and A2M concentration of an Alpha2EQ final concentrate is no different than the volume and concentration of A2M in the PP from Pro-Stride or Restigen devices. f would have to be 2.5 times greater than a Pro-Stride APS final sample to provide an equivalent amount of A2M.